Epikurs Briefsammlung und POxy 76.5077 - Klauck, Hans-Josef (Zeitschrift für die neutestamentliche Wissenschaft, 2019)
Epicurus is well known as the letter writer par excellence among ancient philosophers. This is shown by examples from Alciphron, Diogenes Laertios, Seneca, and Plutarch. Additionally, the long list of partially preserved letters in the collections of fragments by Usener and Arrighetti is analyzed. These quotes demonstrate the use of letter collections originating with Epicurus and his first students. A new valuable testimony is provided by the publication in 2011 of POxy 5077. Its three fragments are clearly taken from a collection of letters of Epicurus. We find his name in a typical prescript: "Epicurus (to NN), greetings". Leonteus and Mithres of the founding generation are mentioned. The copying of letters and the exchange of documents within the Epicurean community are fully on display. The little known shipwreck suffered by Epicurus is alluded to. All this is not without interest for students of early Christian letter collections.